PENGARUH ADANYA TRANSPORTASI ONLINE TERHADAP KESEJAHTERAAN MASYARAKAT MELALUI VARIABEL PENGANGGURAN DI KOTA MEDAN - febi, febi; Alfadri, Ferri (IAIN Langsa, 2018)
Research this aim for conduct direct research related to the influence of the emergence of an online transportation system in the life of the community in terms of aspects of unemployment and also the welfare of the people in Medan City. This research was conducted at PT. GO-JEK Indonesia in Medan, North Sumatra Province with use method quantitative . On research this use technique SEM analysis methods with the help of Smart PLS program. Based on the results of statistical calculations after researched , then can be concluded that: the existence of online transportation has a significant positive effect on the unemployment rate directly. This can be proven from the t-statistics value of 86,750, the existence of online transportation has a significant positive effect on welfare directly. This can be proved from the t-statistics value of 5, 638, and with their online transportation positive 5,638, effect on the welfare of the signifikcant  directly through variable unemployment. This can be proven from the t-statistics value of 4,880. Thus, the H1, H2 and H3 hypothesis in this study was accepted.